A study of autoimmune thyroiditis in thyroid swellings - Reddy, Yugandhar Gollapalli; Surender, Losari (International Surgery Journal, 2019)
Background: The present study aimed to study occurrence, clinical presentation, biochemical status and management strategies, complications and clinical improvement during follow up of autoimmune thyroiditis in patients presenting with thyroid swellings. Methods: The prospective study was carried out from 18 months i.e., from January 2016-June 2017 at Department of General Surgery, Bhaskar Medical College, Yenkapally, Moinabad, Ranga Reddy, Hyderabad, Telangana, India. A detailed clinical history was taken from all patients followed by clinical examination. Following investigations were performed on all patients. Haematological investigations (T3, T4, TSH, thyroid antibodies), fine needle aspiration cytology, Histopathology report and Thyroid scan. Data was analyzed using SPSS software (V.23.0). Results: The occurrence of autoimmune thyroiditis was determined in 15 (22.73%) patients. Most of the patients were females. About clinical presentation; goitre was present in all 66 (100%) cases. In group A; following complications were seen at the time of 1 year follow up: 1(6.67 %) patient developed Graves disease, 2 (13.33%) patients who were initially euthyroid developed hyperthyroidism and thyroid lymphoma was detected in 2 (13.33%) patients. In group B, following complications were seen at the time of 1 year follow up; 4 (7.84%) patients who were initially euthyroid developed hyperthyroidism and 2 (3.92%) patients developed follicular thyroid carcinoma and mortality observed was 1 (1.96%) patient. Conclusions: All cases of goitre should thus be comprehensively evaluated even though they might be asymptomatic.